Identifying Critical Thinking in “My Next Words” for Fifth Grade: A Study Using Content Analysis - Dewi, Milatul Auliya Dewi; Rizky Septian Rahayu; Tria Moulina; Yessi Nurul Rahmi; Lystiana Nurhayat Hakim (Journal of Applied Linguistics (ALTICS), 2024)
This study investigates the presence and development of critical thinking elements within the My Next Words textbook for fifth-grade EFL students. Using content analysis, the research examines the textbook's activities through the lens of Bloom's Taxonomy: Remember, Understand, Apply, Analyze, Evaluate, and Create. Analysis of specific instructions, such as "Look at the picture and write your friend’s activities" and "Describe your activity that you can do in your room," reveals that while the textbook incorporates tasks fostering basic critical thinking skills like recall and application, it falls short in promoting higher-order cognitive processes, including detailed analysis and critical evaluation. To enhance the development of advanced critical thinking skills, future editions should integrate more complex activities that challenge students to engage in deeper cognitive processes. The study underscores the need for a more balanced approach to foster comprehensive critical thinking abilities in EFL education, suggesting that future research should explore the long-term impact of these tasks and the role of teacher training and digital tools in enhancing critical thinking. Keywords: Critical Thinking, Content Analysis, Bloom’s Taxonomy, EFL Instruction, Elementary Education